2016
DOI: 10.1136/ejhpharm-2016-000900
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medication review, within a shared decision-making framework, on deprescribing in people living in care homes

Abstract: ObjectivesThe key objectives of this study were to quantify extent of prescribing, reasons for deprescribing, common therapeutic groups of medicines deprescribed and adverse events.MethodsA retrospective analysis was carried out on a quality improvement project where 422 care home residents in 20 care homes received a medicines optimisation review with a pharmacist and other members of the healthcare team (general medical practitioner, care home nurse). Data on number, type and cost of medicines were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…Pending these guidelines, health professionals can rely on the safety evidence from a small but growing number of deprescribing studies. Indeed, the literature describes only a few cases of necessity for reintroduction of withdrawn or reduced medicines [33]. The evidence of the literature confirms that the clinical skills and knowledge engaged for prescribing and deprescribing are similar.…”
Section: Individual Level: Working On Pedagogy While Respecting Complmentioning
confidence: 90%
“…Pending these guidelines, health professionals can rely on the safety evidence from a small but growing number of deprescribing studies. Indeed, the literature describes only a few cases of necessity for reintroduction of withdrawn or reduced medicines [33]. The evidence of the literature confirms that the clinical skills and knowledge engaged for prescribing and deprescribing are similar.…”
Section: Individual Level: Working On Pedagogy While Respecting Complmentioning
confidence: 90%
“…Implementing shared decision-making between prescribers and patients ( Baqir et al, 2017 ; Bekker, 2018 ) and increasing patient awareness about medication waste ( Bekker et al, 2018b ; Bekker, 2018 ) may also help in minimising medication waste. A study has shown that shared decision-making between prescribers and patients and medicine optimisation reviews can lead to a reduction in polypharmacy and tailor medicines to a patient’s individual needs and thus reduce medication waste arising from unnecessary medications ( Baqir et al, 2017 ). Also, providing information on improving patients’ adherence to medicines and increasing awareness about medication waste that may occur due to non-adherence during consultation may help to tackle the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the dispensing stage, transferring medications close to expiry to other pharmacies that are able to dispense them to patients in time may help in reducing medication waste ( Baqir et al, 2017 ; Bekker, 2018 ). Pharmacies could request medications that are needed and not in stock using an online database and can register medications close to expiratory date on the database.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a case study of medication reviews in care homes involved meetings between residents, family members, care home staff, a pharmacist and (when possible) a GP. 191 Another example of an interprofessional approach to care planning (which involves SDM) comes from the Year of Care initiative when care planning involved a first consultation with a HCA who helped the patient work out 'what they want to do' followed by a second consultation with a GP or specialist nurse to make a care plan. 25 Both reported positive outcomes.…”
Section: Shared Decision-making and The New Models Of Carementioning
confidence: 99%